Conservation and Heritage As Creative Processes of Future-Making. Issue 2 (May 2020) - Holtorf, Cornelius
Abstract: According to the logic of the conservation ethics, the heritage sector has the duty to conserve cultural heritage because it has inherent value and constitutes a non-renewable resource that once destroyed cannot be substituted and, therefore, must be preserved for the benefit of future generations. In this article, I argue, however, that the cultural heritage of the past is not a comprehensive legacy that theoretically, at any point, might have been considered complete but, rather, that it can be understood as frequently updated manifestations of changing perceptions of the past over time. The most important question for conservation and heritage management, thus, is not how much heritage of any one period may or may not survive intact into the future but, instead, which heritage, as our legacy to the generations to come, will benefit future societies the most. In particular, I am calling for more research into the possible significance of heritage in addressing some of the social consequences of climate change.